CCNA security study guide exam 210-260 - McMillan, Troy (Sybex, 2018)
The CCNA Security Study Guide offers comprehensive preparation for Exam 210-260, with expert coverage of all exam objectives and a robust tool kit of learning aids. Providing explanation and insight into the installation, troubleshooting, and monitoring of secure networks, this guide helps candidates develop the technological competency they need to maintain the integrity, confidentiality, and availability of data and devices. Practical examples give you a real-world understanding of critical security issues, and access to the Sybex online interactive learning environment provides chapter tests, electronic flashcards, practice exams, and more to help you maximize your study time while building skills and confidence.